COASTAL CHARACTERISTICS OF IRON SAND DEPOSITS IN INDONESIA - HANANTO KURNIO (Indonesian Mining Journal, 2007)
Coastal features of Indonesia are controlled by the geology and geomorphology of the hinterland and the bordering adjacent marine environments. Tectonic instability manifested as frequent earthquakes combined with volcanic eruptions and sea level changes also affect Indonesian coastline. Unstable air and heavy rainfall zone known as intertropical convergence zone (ITC) which migrates to the north and south of the equator together with orographic factor of mountain ranges in Sumatra, Java and Nusatenggara are also controlling coastal landforms. Large sediment quantities resulted from a com- bination of deeply weathered rock in steep elevated hinterlands and frequent heavy rainfall are trans- ported to the coast and built extensive deltas and broad coastal plains. Iron sands in Sumatra, Java, Bali and Nusatenggara Islands are largely derived from denudation of andesite and old andesite forma- tion enriched in magnetite and ilmenite minerals. In certain cases periodic eruptions of active volca- noes supply fluvial sand to maintain the prograding shoreline. Wave regime in Indonesian coastal waters resulted from strong swells of Indian Ocean in the south and Pacific Ocean in the northeast has much influence various coastal features. Coastal zones especially the southern parts of the Neogene Sunda Banda magmatic arc are the area of potential and producing iron sand deposits which extend from northern Sumatra to eastern Indonesia. Beach sediments enriched in magnetic minerals of such coastal zones are typically black or grey. The iron sand deposits have been mined either by state company or by local people. Small scale mining helps to improve the economy of the commu- nity. Application of regulations and good guidances of these artisanal minings will not destructive to the natural environments.